Deepfake Satire and the Possibilities of Synthetic Media. - GLICK, JOSHUA (Afterimage, 2023)
This article explores the rise of deepfake satire as one of the most vibrant subgenres of experimentation within the expanding field of AI art. A combination of "deep learning" and the word "fake," deepfake videos depict people doing or saying things that they never did or said. While deepfakes have been used to deceive and harm individuals as well as a mass audience, they have also been used toward alternative ends. Deepfake satire offers artful social critique, interrogating the individuals and institutions it portrays as much as the technology used to create it and the platforms on which it circulates. Videos range from snarky jabs at entertainment industry personalities to hard-hitting takedowns of tech entrepreneurs and authoritarian leaders. This speculative form of social imagining makes threatening and seemingly untouchable figures appear weak, vulnerable, and exposed, which can help envision a more equitable and just future. Close examination of specific projects within a broader media ecology leads to a nuanced understanding of both the menace and progressive possibilities of synthetic media--beyond simple "utopia"/"dystopia" binaries--in addition to expanding the grammar of computational art.